A quasi-experimental study to assess the effectiveness of planned teaching programme on knowledge regarding the electroconvulsive therapy among family members of patients with mental illness - Shalini, Shalini; Apte, Sundari (International journal of health sciences, 2022)
Effectiveness of planned teaching programme on knowledge regarding the Electroconvulsive therapy among family members of patients with mental illness Objectives were to assess the pre-test knowledge level about electroconvulsive therapy among family members of patients with mental illness in both control and experimental group; To assess the post-test knowledge level about electroconvulsive therapy among family members of patients with mental illness in both control and experimental group; To determine the effectiveness of planned teaching programme on electroconvulsive therapy among family members of patients with mental illness. And to associate pre-test knowledge level on electroconvulsive therapy among family members of patient with mental illness with selected demographic variables. Methodology: The study was quantitative in approach and the design was Quasi-Experimental with pre test post test control group. The sample size was 60 each in experimental & control. Family members of mentally ill patients are population for this study. A Non-probability purposive sampling technique was used to select the samples. Data was collected by using the tools which consisted of demographic data sheet and Knowledge score on electroconvulsive therapy which consisted of 30 questionnaires.